Admiralty law in South Africa: section 6 of the Admiralty Jurisdiction Act - an analysis, comparison and case law examination - Stiebel, Mark (Department of Commercial Law, 2023)
Under South African Admiralty law the Courts are to apply two different systems of law depending upon whether the matter could have been heard under the old jurisdiction held by the Colonial Courts of Admiralty as at 1890. If the matter does involve this old jurisdiction then English law as it was in 1983 must be applied by the Courts to the matter. If the matter involves a new jurisdiction, which was unknown in the old courts, then Roman-Dutch law must be applied to the matter. These dual systems of admiralty have resulted in interesting judicial application, with certain judges correctly applying the statute, while others have ignored or chosen not to follow its directives. This paper investigates how admiralty law has developed in South Africa resulting in the dual system and analyses the mechanism established through legislation. The application through case law of the section is analyzed to discover how the section has been utilized by the South African courts. Thereafter a comparison is made of other jurisdictions with a similar admiralty source to discover how they have resolved the juxtaposition of admiralty law with domestic law. Suggestions for legislative reform are suggested and debated.